Psychometric Study of the advanced form of the Raven’s Progressive Matrices Test in university students - Delgado Vasquez, Ana (2001)
It is analized the psychometric properties of Raven’s Advanced Progressive Matrices. The participants were 501 Freshmen students of 5 professional careers of the Universidad Nacional Mayor de San Marcos (U.N.M.S.M.), a public university located at Lima, Perú. The reliability analysis shows that the test is reliable. Also, the construct validity analysis meets the requirements of test making. The norms were elaborated considering the professional careers of the U.N.M.SM. students. It was find statistical differences on general intelligence scores, showing higher scores students of career “B” than students of “A “, “C “, “D” and “E” careers; also, students from career “C” showed higher scores than students from “A” and “E” career paths; finally, students from professional career“D” have had higher scores than students of “A“ and “E” careers. It was find no statistical differences between students of career “A” and “E “; neither between students of “C” and “G” career paths.